Analisis Kesulitan Guru dalam Menyusun Instrumen Penilaian Pembelajaran - Ikhlas Abas; Ita Desmayani; Rosdiana; Mustaqim Hasan (Advances In Education Journal, 2026)
Learning assessment is a fundamental component of the educational process as it serves as the basis for determining the comprehensive achievement of students' competencies. In practice, teachers are required to develop assessment instruments that are valid, reliable, and aligned with learning objectives. However, various studies indicate that many teachers still face difficulties in designing assessment instruments, particularly in constructing test blueprints, formulating indicators, developing attitude and skill instruments, and designing Higher Order Thinking Skills (HOTS)-based questions.This article aims to analyze teachers' difficulties in developing learning assessment instruments, the influencing factors, and the strategies that can be implemented to enhance teacher competence. This study employs a literature review approach by examining relevant literature on learning assessment, evaluation instruments, and teacher competence. The results of the study show that teachers' difficulties are influenced by internal, organizational, and curricular factors, as well as student characteristics. To address these issues, continuous training, professional mentoring, the utilization of technology, the development of an instrument bank, and a more proportional workload management are required. Thus, enhancing teacher competence in developing assessment instruments is a crucial step toward producing objective and comprehensive learning evaluations.